Teacher Efforts to Increase Student Motivation in Memorizing the Quran - Ringgit, Awang; Putri, Rahmadani; Sari, Istiqomah Wulan; Putri, Ramona Eka (International Journal of Multidisciplinary Research of Higher Education, 2020)
Being a memorizer of the Quran is a noble job. Therefore, motivation is needed that is obtained from the family environment, friends' environment, and school environment. So in this case, the teacher plays an important role in every student's learning process including motivating students to memorize the Quran. This study aims to determine the efforts of tahfidz teachers in increasing the motivation for memorizing the Quran for class VI at integrated Islamic elementary school Cahaya Quran. This research uses a qualitative method with a case study approach. Data sources were taken from seven informants consisting of tahfidz teachers and students with in-depth interviews who were selected using purposive sampling techniques. The research findings show six teacher efforts in increasing motivation to memorize the Quran for class VI at integrated Islamic elementary school Cahaya Quran, namely: i) giving motivational words to students, ii) giving prizes, iii) giving assignments or targets for memorizing & giving punishments to students, iv) guiding students to always murajaah, v) hold tahfidz graduations, and vi) use the tikrar method. The results of this study can be used as information for the community so that they can increase motivation for memorizing the Quran for children.